Cranial findings detected by second‐trimester ultrasound in fetuses with myelomeningocele: a systematic review. (3rd January 2021) - Kunpalin, Y; Richter, J; Mufti, N; Bosteels, J; Ourselin, S; De Coppi, P; Thompson, D; David, AL; Deprest, J
Abstract : Background: Abnormal intracranial findings are often detected at mid‐trimester ultrasound (US) in fetuses with myelomeningocele (MMC). It is unclear whether these findings constitute a spectrum of the disease or are an independent finding, which should contraindicate fetal surgery. Objective: To ascertain the spectrum and frequency of US‐detected cranial findings in fetuses with MMC. Search strategy: MEDLINE, Embase, Web of Science and CENTRAL were searched from January 2000 to June 2020. Selection criteria: Study reporting incidence of cranial US findings in consecutive cases of second‐trimester fetuses with MMC. Data collection and analysis: Publication quality was assessed by Newcastle–Ottawa Scale (NOS) and modified NOS. Meta‐analysis could not be performed as a result of high clinical diversity and study heterogeneity. Main results: Fourteen cranial US findings were reported in 15 studies. Findings in classic Chiari II malformation (CIIM) spectrum included posterior fossa funnelling (96%), small transcerebellar diameter (82–96%), 'banana' sign (50–100%), beaked tectum (65%) and 'lemon' sign (53–100%). Additional cranial findings were small biparietal diameter (BPD) and head circumference (HC) (<5th centile; 53 and 71%, respectively), ventriculomegaly (45–89%), abnormal pointed shape of the occipital horn (77–78%), thinning of the posterior cerebrum, perinodular heterotopia (11%), abnormal gyration (3%), corpus callosum disorders (60%) and midline interhemispheric cyst (42%). Conclusions: We identified 14 cranial findings by second‐trimester US in fetuses with MMC. The relatively high incidence of these findings and their unclear prognostic significance might not contraindicate fetal surgery in the case of normal fetal genetic testing. Some cranial findings may independently affect postnatal outcome, however. Long‐term detailed follow‐up is required to investigate this. Tweetable abstract: A high rate of cranial abnormalities found on second‐trimester ultrasound in fetuses with myelomeningocele. Tweetable abstract: A high rate of cranial abnormalities found on second‐trimester ultrasound in fetuses with myelomeningocele.